Guyana’s paediatric training program: a global health partnership for medical education - Cameron, Lita; Johnston, Julie; Sparman, Arnelle; Nelin, Leif D; Singh, Narendra; Hunter, Andrea (Revue canadienne de l’éducation médicale, 2017)
Guyana is a low-middle income country on the northern coast of South America between Venezuela and Suriname. Guyana has relatively high child mortality and a notable gap in health care provision. As of 2011, there were no paediatricians in the public sector where approximately 90% of the population seek care. In response to this unmet need, Guyanese diaspora living in Canada, in partnership with Canadian paediatricians and the main teaching hospital, Georgetown Public Hospital Corporation (GPHC), developed a Master’s program in paediatrics. The postgraduate program was designed with adapted training objectives from the Royal College of Physicians and Surgeons of Canada and the American Board of Paediatrics. Innovative strategies to overcome the lack of qualified paediatric faculty in Guyana included web-conferencing and a volunteer North American paediatric faculty presence at GPHC with a goal of 1-2 weeks every month. By November 2016, 10 graduates will have passed through a rigorous program of assessment including a two-day final examination with an objective structured clinical examination (OSCE) component.